Design of optimum system of viscoelastic vibration absorbers with a Frobenius norm objective function - Espíndola,José J. de (2009)
Vibration absorbers, also called vibration neutralizers, are mechanical systems to be attached to another mechanical system, or structure, called the primary system, with the purpose of reducing vibration and sound radiation. The simplest form of a vibration absorber is that of a single degree of freedom system, where the "spring" is made of a viscoelastic material, perhaps with some metallic inserts. This paper sets out to describe how to design a best possible system of viscoelastic vibration absorbers for an available viscoelastic material, known by its four fractional parameter model, by using a novel objective function, defined through a Frobenius norm. A real example is presented and discussed.